ASPEK-ASPEK GRAMATIKAL YANG TERLEWATKAN DALAM PENYUSUNAN TATA BAHASA INDONESIA - I Wayan Pastika (Adabiyyāt: Jurnal Bahasa dan Sastra, 2013)
Many controversial issues on Indonesian grammar need to discuss to be more detail and four of the most crucial ones are: (a) the morphophonemic processes of the active voice marker, (b) the degree of transitivity for the causative and applicative, (c) the third passive other than di- and ter-, and (d) different types of reflexive. The classical Generative Grammar is applied to approach the first issue, while Typological theory is employed for the three other problems. The objective is to propose a new concept on how the grammatical structure is determined. The norm of morpheme for the active voice marker is meng- since it occurs with a wider distribution, while mem-, men-, meng-, me- and menge- occur in particular phonological environments. In the causative –kan and the applicative –i, the -kan is more transitive than the -i. The construction of OAV in this paper is called the third passive, other than the passive di- and ter-. For the reflexive, it has to be distinguished into transitive with a real Object and pseudo Object. The first type can be passived while the second type is not allowed. Reflexive also takes intransitive where the Subject is Doer and Undergoer at the same time.